PENINGKATAN PROFESIONALISME GURU DALAM PERSEPEKTIF BUDAYA RELIGIUS - Abdul Rosyid; Fatkhul Mubin (Alim | Journal of Islamic Education, 2022)
This study aims to analyze 1) the implementation of religious culture in MTs Negeri 12 Jakarta, 2) teacher professionalism in MTs Negeri 12 Jakarta, 3) efforts to improve teacher professionalism through management based on religious culture in MTs Negeri 12 Jakarta. The results found in this study are that 1) the implementation of religious culture-based management in schools can be stated, that every teacher is disciplined in carrying out his duties both, in the learning process and outside of learning. In this case the principal performs several stages or steps, namely; starting from planning, organizing, implementing, and supervising, 2) teacher professionalism in making learning tools, learning processes, and assessments classified as good and professional, 3) efforts to increase teacher professionalism through religious culture-based management that is well displayed and applied in improving teacher professionalism, namely: discipline, example, togetherness, congregational prayers accompanied by students, and tilawah.